Prediksi Penjualan Metal Roof menggunakan Metode Backpropagation (Studi Kasus: PT Comtech Metalindo Terpadu) - Vandi Cahya Rachmandika; Muhammad Tanzil Furqon; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The manufacturing industry in Indonesia has developed rapidly in line with technological developments in Indonesia. The manufacturing industry that has experienced an increase is the printed goods industry. In this research, one of the printed goods industries is PT Comtech Metalindo Terpadu is a metal roof sales industry. PT Comtech Metalindo Terpadu has a problem regulating the supply of metal roof raw materials. In this case, predicting metal roof sales can find out sales at a certain period, so that it can help to regulate raw material inventory or purchase of raw materials. This study uses the Backpropagation method to predict sales of metal roofs, and to evaluate the predictive error value will use the Mean Absolute Precentage Error (MAPE). The smallest MAPE value obtained from this study is 5.76% with the neuron input value 3, the hidden neuron value 100, the initial weight range value in the range -0.5 to 0.5, the learning rate value 0.2, and the epoch value 150.